Large-scale desalination based on parabolic trough collectors and double-effect absorption heat pumps. (November 2020) - Colmenar-Santos, Antonio; León-Betancor, Andrés; Diez-Suárez, Ana-María; González-Martínez, Alberto; Rosales-Asensio, Enrique
Abstract: This paper focuses on an analysis of the current situation of distillation and reverse osmosis technologies and their relationship with renewable energies, to the extent that there is a strong trend in the use of distillation and reverse osmosis technologies. Large-scale seawater desalination using renewable energy is not developed, so a detailed study of the combination of renewable energy facilities, reverse osmosis, and distillation systems are needed to be effective and competitive compared to the use nonrenewable energy. Solar multiple is a very important parameter in the solar thermal industry. This is in the range of 1.5 – 3 and depends on the relationship between storage and plant power. This parameter is important because it reflects a balance between the cost of the parabolic trough collectors and the total of the solar thermal plant. If the same criterion is followed, with a thermal gap of 100 °C, chosen for the parabolic trough collectors sizing, the solar multiple in the system object of this article, has a value higher than 3. The proposed system employs renewable energies for reducing the downtime of the desalination plants, doing possible that the desalination plants being competitive in sites with poor quality solar radiation.